Analisis CPUE (Catch Per Unit Effort) dan Potensi Lestari Sumberdaya Perikanan Tembang (Sardinella fimbriata) di Perairan Selat Sunda - Nidya Kartini; Mennofatria Boer; Ridwan Affandi (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2021)
Sunda Strait has high values of fish resources, one of the resource are fringescale sardinella (Sardinella fimbriata). Catches composition for fringescale sardinella was 26% and the largest among the composition of other small pelagic fish. Management of fish resources needs to be carried out in a controlled manner followed by monitoring of the sustainability fish resources. This study aims to analyze the value of CPUE, assess the status of the stock, and total allowable catch of fringescale sardinella in the Sunda Strait. The method used in this research was descriptive method. The results showed that the relationship between effort and CPUE of tembang fish had a determination value (R2) of 85% with the equation CPUE = -0,0003F + 1,616. The MSY value using the Schaefer model approach was 2608,65 tons / year and optimal effort (fMSY) was 3.227 trips, actual catch was 2382,46 tons/ year, actual effort was 4015 trips, and total allowable catch (TAC) was 2347,78 tons. Keywords : CPUE, fringescale sardinella, sustainable yield, Sunda Strait